2011
DOI: 10.2174/156802611794785163
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Natural Products as Iron Chelators

Abstract: An evaluation of existing and proposed Fe chelators, both synthetic and natural products, for the treatment of Fe-overload disease must address a number of issues. There are fundamental parameters that determine the efficacy of a drug: absorption, distribution, metabolism, clearance and toxicity. However, the administration of chelator for Fe overload aims to generate Fe complexes in vivo that are able to be excreted. Hence, the chemical and pharmacological properties of the complexes formed are equally import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 130 publications
0
12
0
1
Order By: Relevance
“…Recent investigations have focused on the development of novel Fe chelators, where di-2-pyridylketone thiosemicarbazone and 2-benzoylpyridine thiosemicarbazone were found to have potential applications in the treatment of cancer [170]. There are also many kinds of synthetic and natural products with the potential to serve as iron chelators [171,172]. Taken together, the results of these studies suggest that Fe-overload diseases can be controlled efficiently by treating with specific chelators.…”
Section: Ironmentioning
confidence: 99%
“…Recent investigations have focused on the development of novel Fe chelators, where di-2-pyridylketone thiosemicarbazone and 2-benzoylpyridine thiosemicarbazone were found to have potential applications in the treatment of cancer [170]. There are also many kinds of synthetic and natural products with the potential to serve as iron chelators [171,172]. Taken together, the results of these studies suggest that Fe-overload diseases can be controlled efficiently by treating with specific chelators.…”
Section: Ironmentioning
confidence: 99%
“…Number of preclinical anticancer lead compounds obtained from marine-derived organism has been increasing rapidly in last few years [11-13]. In many cases the natural occurring compounds are more effective and do not have considerable undesired consequences compared with synthetic drugs [14]. Compounds from natural source are studied extensively with respect to structural modification in order to explore their further use in pharmacy and medicine in the prevention and treatment of cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Investigations by our laboratories have shown that they form stable Fe II complexes, in contrast to the Fe III complexes formed by DFO, deferiprone and deferasirox. 1,2,4 Subsequent studies have shown that substitutions to the C-atom adjacent to the pyridyl ring lead to a marked change in biological activity, for example the HPCIH analogues based on 2-acetylpyridine (HAPIH series) 17 or di-2-pyridyl ketone (HPKIH analogues) 18 exhibit significant cytotoxicity in contrast to the benign HPCIH chelators. 16 Although deleterious for the treatment of chronic Fe overload (where chelators must be administered lifelong), cytotoxic Fe chelators may prove to be a novel and effective method in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%